MERANCANG MANAJEMEN SUMBER DAYA INSANI IBU RUMAH TANGGA, REMAJA DAN ANAK-ANAK DI DESA KAREHKEL KECAMATAN LEUWILIANG, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Azizah Mursyidah; Erika Apriani (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2022)
This community service was carried out in Karehkel Village, Leuwiliang District, Bogor Regency. This community service aims to develop Human Resources and the potentials that exist in Karehkel Village, especially mothers, adolescents and children. In community service this is done by the method of observation, training, interviews and application implementation. The community is also enthusiastic about this community service activity, because they gain an insightful understanding of human resource development, especially in developing the abilities of mothers, adolescents and children.